2015
DOI: 10.1016/j.ejphar.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The activation of PI 3-kinase/Akt pathway is involved in the acute effects of simvastatin against ischaemia and reperfusion-induced arrhythmias in anaesthetised dogs

Abstract: The objective of this study was to examine whether the PI3-kinase/Akt pathway is involved in the activation of endothelial nitric oxide synthase (eNOS) and in the subsequent increase of nitric oxide (NO) production that has been proved to play a role in the antiarrhythmic effect of acute simvastatin treatment in anaesthetised dogs, subjected to a 25min occlusion and reperfusion of the left anterior descending coronary artery. Using the same model, 12 dogs out of the 26 controls (given the solvent of simvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The substantial role and investigation of precise mechanisms of NO, both under physiological or pathological conditions, are not a question of debate in cell signaling and myocardial function. A number of studies show that interventions contributed to NO production via different mechanisms significantly reduced the reperfusion-induced injury including the incidence of arrhythmias (Shen et al, 1998;Kawahara et al, 2003;Imaizumi et al, 2008;Egom et al, 2011;Kisvari et al, 2015;Enayati et al, 2018;Jones et al, 2018). Various protective NO-mediated signal mechanisms, including the mitoK-(ATP) (Kawahara et al, 2003), the nuclear factor erythroid 2-related factor (NrF2), the extracellular-signalingregulated-kinase (ERK) (Imaizumi et al, 2008), and Pak1/Akt1 signaling cascade (Egom et al, 2011) have also been reported.…”
Section: No Co H 2 S (Gaseous Molecules)mentioning
confidence: 99%
“…The substantial role and investigation of precise mechanisms of NO, both under physiological or pathological conditions, are not a question of debate in cell signaling and myocardial function. A number of studies show that interventions contributed to NO production via different mechanisms significantly reduced the reperfusion-induced injury including the incidence of arrhythmias (Shen et al, 1998;Kawahara et al, 2003;Imaizumi et al, 2008;Egom et al, 2011;Kisvari et al, 2015;Enayati et al, 2018;Jones et al, 2018). Various protective NO-mediated signal mechanisms, including the mitoK-(ATP) (Kawahara et al, 2003), the nuclear factor erythroid 2-related factor (NrF2), the extracellular-signalingregulated-kinase (ERK) (Imaizumi et al, 2008), and Pak1/Akt1 signaling cascade (Egom et al, 2011) have also been reported.…”
Section: No Co H 2 S (Gaseous Molecules)mentioning
confidence: 99%
“…Statins also protect other tissues in the presence of IR, such as heart [ 17 - 19 ] , nervous system [ 20 ] and liver [ 21 ] . In the lung, the efficiency of statins was also demonstrated, as published by Matsuo et al [ 22 ] , however, with a method different from the one used here, since these authors performed IR directly in the pulmonary hilum, thus not being a study of remote protection.…”
Section: Discussionmentioning
confidence: 99%
“…Statins also protect other tissues in the presence of IR, such as heart 6 , 9 , 10 , nervous system 5 and lung 14 . The protection mechanism of statin against situations of IR is due to its pleiotropic effect.…”
Section: Discussionmentioning
confidence: 99%